2011
DOI: 10.1177/1468087411403854
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fuel properties on thermal efficiency of advanced spark-ignition engines

Abstract: Owing to issues of global warming and energy security, improving engine thermal efficiency has become increasingly important today. This paper investigates the impact of high-research-octane-number (RON) fuels on engine thermal efficiency. It is shown that the lean boosted engine has higher potential to increase engine thermal efficiency than naturally aspirated (NA) engines and the combination of lean boosted engine and high-RON fuels gives around 44 per cent engine thermal efficiency. The engine thermal effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In Table 6, the physical properties of ethanol and methanol, as values or a range of values, according to authors from 10 references cited in their paper review [1]. Also, values from [8,12,13,25,29,69,[86][87][88][90][91][92][93] were taken into account. As before, those values that go well beyond the range found in most of the references are italicized, together with their references.…”
Section: Bio-ethanol/bio-methanol Physico-chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 6, the physical properties of ethanol and methanol, as values or a range of values, according to authors from 10 references cited in their paper review [1]. Also, values from [8,12,13,25,29,69,[86][87][88][90][91][92][93] were taken into account. As before, those values that go well beyond the range found in most of the references are italicized, together with their references.…”
Section: Bio-ethanol/bio-methanol Physico-chemical Propertiesmentioning
confidence: 99%
“…Nakata et al [29] have shown the improved effect of using bio-ethanol upon the thermal efficiency of an SI engine, thanks to the its higher Research Octane Number (RON); consequently, they have considered that using alcohols in a lean boosted engine (i.e., a turbocharged engine operating with lean mixture) could be one of the future technologies for road mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated ethanol (or E85) engines have the promise to improve efficiency substantially over comparable regular gasoline engines through direct-injection, increased geometric CR, variable valve timing, exhaust gas recirculation, aggressive turbocharging, and downsizing and/or downspeeding. It has also been demonstrated that lean boosted engines with ethanol can produce efficiency higher than that offered by diesel engines …”
Section: Resultsmentioning
confidence: 99%
“…101−107 It has also been demonstrated that lean boosted engines with ethanol can produce efficiency higher than that offered by diesel engines. 108 The increased engine efficiency at high load for ethanol/ gasoline blends (as a result of their antiknock properties) could also be explored in hybrid-electric powertrains (with a much narrower and optimized engine operating regime), 105 as shown in a simulation study on a series plug-in hybrid vehicle. 109 Some innovative engine concepts and designs such as the Direct Injection Ethanol Boosted Gasoline Engine (DIEBGE) show great promise of improving the efficiency of gasoline use through the leverage effect of ethanol and thereby maximize the potential benefits from a limited amount of ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Many approaches have been proposed, including exploiting fuel effects, as highlighted by Manente et al, 8 who explored using low-reactivity gasoline in LTC compression ignition engines, and Xu et al, 9 who considered using onboard fuel-reforming technologies and the application of supercharging combined with trapping of residual gases for improved fuel–air preparation. As pointed out by Nakata et al, 10 lean boosted spark-ignition engines, fueled with high-research-octane-number (RON) fuels, are also of considerable interest, and they can exhibit thermal efficiencies comparable to those of diesel engines.…”
mentioning
confidence: 99%